2019
DOI: 10.1021/acs.nanolett.9b01007
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Growth of Pure Wurtzite and Zinc Blende Nanowires

Abstract: The opportunity to engineer III–V nanowires in wurtzite and zinc blende crystal structure allows for exploring properties not conventionally available in the bulk form as well as opening the opportunity for use of additional degrees of freedom in device fabrication. However, the fundamental understanding of the nature of polytypism in III–V nanowire growth is still lacking key ingredients to be able to connect the results of modeling and experiments. Here we show InP nanowires of both pure wurtzite and pure zi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 70 publications
0
19
0
Order By: Relevance
“…A nanowire FET device has great potential to achieve advanced device performance, with tunable channel characteristics and flexible device configuration . From the synthesis viewpoint, typical vapor deposition technology facilitates a high yield of nanowires of uniform quality as well as a high degree of controllability of the nanowire thickness, length, crystal structure, and defects . Additionally, a nanowire derived from deposition methods with an epitaxial relationship to the semiconductor substrate facilitates gate‐all‐around technology that displays more effective gate‐voltage control .…”
Section: Nanowire Electronicsmentioning
confidence: 99%
See 3 more Smart Citations
“…A nanowire FET device has great potential to achieve advanced device performance, with tunable channel characteristics and flexible device configuration . From the synthesis viewpoint, typical vapor deposition technology facilitates a high yield of nanowires of uniform quality as well as a high degree of controllability of the nanowire thickness, length, crystal structure, and defects . Additionally, a nanowire derived from deposition methods with an epitaxial relationship to the semiconductor substrate facilitates gate‐all‐around technology that displays more effective gate‐voltage control .…”
Section: Nanowire Electronicsmentioning
confidence: 99%
“…47 From the synthesis viewpoint, typical vapor deposition technology facilitates a high yield of nanowires of uniform quality as well as a high degree of controllability of the nanowire thickness, length, crystal structure, and defects. 28 Additionally, a nanowire derived from deposition methods with an epitaxial relationship to the semiconductor substrate facilitates gate-all-around technology that displays more effective gate-voltage control. 32,48 Benefiting from the huge specific surface area of nanowires, doping and heterostructure interface engineering can largely promote the device's figures of merit (such as mobility, transconductance, on-off ratio, and threshold voltage).…”
Section: Nanowire Fetsmentioning
confidence: 99%
See 2 more Smart Citations
“…107 Even grown on non-(1 ̅ 1 ̅ 1 ̅ ) substrate plane, it can be found that nanowires were inclined to align themselves along [1 ̅ 1 ̅ 1 ̅ ]/[0001 ̅ ]. [108][109][110][111] However, the nucleation energy difference between WZ and ZB is quite small at (1 ̅ 1 ̅ 1 ̅ ) or (0001 ̅ ) catalyst-nanowire interface, which undesirably leads to the mixture of WZ and ZB (i.e. polytypism) in nanowires.…”
Section: Nanowire Growth Orientationmentioning
confidence: 99%